Implementasi Sistem Informasi Akuntansi Dan Akuntabilitas Pengelolaan Dana Bos Reguler - Nurul Farida; Mulyaningtyas (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2024)
This study aims to find out and evaluate whether the Implementation of Accounting Information Systems and Accountability for Regular School Operational Assistance (BOS) at SMP Plus Hidayatul Mubtadiin Singosari is by "Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia number 2 of 2022" concerning Technical Instructions BOSS. The analysis tool uses a qualitative descriptive method. The research shows that the implementation of accounting information systems and accountability for regular BOS funds at SMP Plus Hidayatul Mubtadiin in 2022 has worked well according to the Regulations of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia. However, there are still some areas for improvement, such as a lack of parental involvement in students in the BOS financial management process, delays in the disbursement of funds, and the existence of multiple roles related to the responsibilities of the Treasurer.